Una modernità ambivalente. Horkheimer e la ristrutturazione della critica dell’epoca borghese - Micaloni, Luca (Studi Politici, 2022)
n this paper I will argue that the early “program” of Critical Theory revolves around the concept of a radical ambivalence of the Modern Age. Particularly in Horkheimer’s essays, modernity is split into coexisting and contradictory drives towards liberty and authority, rationality and irrationality, knowledge and faith. Resolving such a tension would entail further rationalization, which the ruling class and its intellectuals prevent by clinging to positivistic or irrationalist justification of the status quo. I will maintain that, though rooted in Marx’s account of the interplay between productive forces and relations of production (and of capitalist development and crisis), Horkheimer’s theses on the limits of bourgeois rationalization diverge from the Marxian ones, inasmuch as they acknowledge significant changes in class consciousness in the era of State monopoly capitalism. Lastly, I will point out a major shift in Critical Theory, from the critique of modernity to a critique of civilization.